2019
DOI: 10.1111/csp2.8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of the impact of a payment for environmental services program on deforestation

Abstract: Despite calls for greater use of randomized control trials (RCTs) to evaluate the impact of conservation interventions; such experimental evaluations remain extremely rare. Payments for environmental services (PES) are widely used to slow tropical deforestation but there is widespread recognition of the need for better evidence of effectiveness. A Bolivian nongovernmental organization took the unusual step of randomizing the communities where its conservation incentive program (Watershared) was offered. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…; Wiik et al. ). More commonly, where this is not possible or desirable, good practice should be to explore and consider potential controls using matching from as early as possible.…”
Section: Moving Forwardmentioning
confidence: 98%
See 1 more Smart Citation
“…; Wiik et al. ). More commonly, where this is not possible or desirable, good practice should be to explore and consider potential controls using matching from as early as possible.…”
Section: Moving Forwardmentioning
confidence: 98%
“…; Wiik et al. ). However, methodological advances to improve causal inference from nonexperimental data have helped to better attribute conservation impacts (Ferraro & Hanauer ).…”
Section: Introductionmentioning
confidence: 98%
“…Between the 1960s and early 2000s, deforestation in the Bolivian lowlands increased from about 4.7x10 4 hectares/year to more than 2.9x10 5 hectares/year (Killeen et al 2008). During the ten years prior to our baseline survey, deforestation in our specific study area was approximately 4,147hectares, with a mean deforestation rate of 1.2% per community (Wiik et al 2019). The goal of the Watershared program was to limit forest degradation, as well as deforestation.…”
Section: The Intervention: Watersharedmentioning
confidence: 99%
“…Pynegar et al (2018) examined the impact of the intervention on water quality (in terms of E. coli contamination of water used for human consumption) and found no impact. Wiik et al (2019) showed that the intervention had limited impact on slowing deforestation (using the Global Forest Change data).…”
Section: A Randomized Controlled Trial In Boliviamentioning
confidence: 99%
“…Strict experiments in applied ecology (Box 1) are generally conducted at small spatial scales (although there are some notable exceptions, e.g. Krebs, Boutin & Boonstra 1995;Wiik et al 2019). This contrasts the fact that many ecological and policy processes operate at far larger scales (Estes et al 2018).…”
Section: A Mature Research Community Should Value Both Exploration Anmentioning
confidence: 99%